Perencanaan Alat Uji Impact Type Charpy Kapasitas 10 Joule - Saktiawan, Saktiawan; Endriatno, Nanang; Imran, Al Ichlas (Teknik Mesin Universitas Halu Oleo, 2020)
In the implementation of construction and material engineering, the choice of materials for metal material needs is very important. The research objectives were planning the pendulum, swing shaft, the frame for the Charpy type impact test, and planning the test specimen holder. The research method includes planning the pendulum, shaft, arm, bearing, pole frame and specimen holder (anvil), as well as selecting materials and calculating the strength of the materials. The results of the research. The impact test tool uses a pendulum made of steel ST 37 with a pendulum length = 0.345 mm, volume = 213 mm3, mass = 1.67 kg, in the planning of the shaft, with the results of the planning calculation obtained the diameter of the shaft = 25.4 mm, while the moment torque obtained = 577,219 kg mm, in the planning of the Charpy type impact test, the frame uses C-profile steel with a size of 125 x 65, the material is chosen because its width exceeds the bearing holder, for tangsial force = 28,951 N, bending moment = 5240.1 N mm , cross-sectional modulus = 109.169 mm3, the specimen holder planning must exceed the specimen width itself so that the specimen can be placed properly, the allowance = 1.206 mm2 and the planning of the impak test tool for the 10 J tool can be used to test plastic materials with an impact energy below 10 J, with a height of 610 ± 2 mm. Keywords: Construction, Materials Engineering, Metal Materials, Iron, Steel, Impak.